Analisis bibliometrik tren penelitian strategi pemasaran perpustakaan tahun 2005 – 2025 - Nurcahyani, Desi; Erwina, Wina; CMS, Samson (Libraria: Jurnal Ilmu Perpustakaan dan Informasi, 2025)
This study aims to analyze the development of research on library marketing strategies from 2004 to 2024 using a bibliometric approach. A quantitative descriptive bibliometric method was employed, with data retrieved from the Scopus database using the keywords "marketing strategy" and "library", resulting in a total of 250 documents. The data were analyzed and visualized using Biblioshiny and VOSviewer. The findings reveal significant fluctuations in publication trends over the past two decades, with notable peaks in 2013 and 2019, and sharp declines in 2020 and 2024. The average citations per year have shown an upward trend since 2022, reaching a peak of 2.2 in 2024. Emerald Emerging Markets Case Studies emerged as the most prolific journal, publishing 102 documents. Quoquab F was identified as the most productive author, with five publications and a fractionalized score of 1.67. The most influential publication, with 55 citations, was authored by Gül Bayraktaroğlu and Özge Özgen, titled “Integrating the Kano model, AHP and planning matrix: QFD application in library services.” Keyword analysis revealed frequent use of terms such as “marketing,” “library marketing,” “strategic marketing,” and “digital marketing,” reflecting the central focus of the research landscape. Institutionally and geographically, Universiti Teknologi Malaysia led in publication output with 14 articles, while the United States and India were identified as the most significant contributing countries. Keywords: bibliometric analysis; marketing strategy; library.